Marketing analysis of brand Yves Saint Laurent in portfolio L´Oréal - Petránková, Tereza; Postler, Milan, 1960-; Bartošová, Gabriela; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
The aim of this thesis Marketing analysis of brand Yves Saint Laurent in portfolio L'Oréal is analysis of brand Yves Saint Laurent. The theoretical part focuses mainly on marketing, brand, luxury, analysis of brand and marketing strategies. Practical part based on the findings in theoretical part analysed brand - history, indentity, value and marketing strategy and reccomend new marketing strategies.
Vedoucí práce: Milan Postler
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses